2020
DOI: 10.1111/nph.16650
|View full text |Cite
|
Sign up to set email alerts
|

Devastating intimacy: the cell biology of plant–Phytophthora interactions

Abstract: An understanding of the cell biology underlying the burgeoning molecular genetic and genomic knowledge of oomycete pathogenicity is essential to gain the full context of how these pathogens cause disease on plants. An intense research focus on secreted Phytophthora effector proteins, especially those containing a conserved N-terminal RXLR motif, has meant that most cell biological studies into Phytophthora diseases have focussed on the effectors and their host target proteins. While these effector studies have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 129 publications
1
75
0
Order By: Relevance
“…Previous reports have demonstrated that P. infestans can enter the leaf either via stomata or by penetrating the periclinal wall of epidermal cells, and the colocalization of some defence proteins in guard cells may function as a preformed defence barrier (Judelson and Ah‐Fong, 2019; Hoegen et al, 2002; Li et al, 2015). Recently, Boevink et al (2020) suggested that the sporangiophores of P. infestans commonly emerge through stomata, and this must involve manipulation of stomatal regulation. In this context, our results show that StLTP10 exhibits a cooperative action with PYL4 to regulate stomatal closure during P. infestans infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have demonstrated that P. infestans can enter the leaf either via stomata or by penetrating the periclinal wall of epidermal cells, and the colocalization of some defence proteins in guard cells may function as a preformed defence barrier (Judelson and Ah‐Fong, 2019; Hoegen et al, 2002; Li et al, 2015). Recently, Boevink et al (2020) suggested that the sporangiophores of P. infestans commonly emerge through stomata, and this must involve manipulation of stomatal regulation. In this context, our results show that StLTP10 exhibits a cooperative action with PYL4 to regulate stomatal closure during P. infestans infection.…”
Section: Discussionmentioning
confidence: 99%
“…After treatment with the same concentration of ABA, the stomata of StLTP10-overexpressing leaves were more susceptible to ABA than those of WT leaves, while the stomata of (Judelson and Ah-Fong, 2019;Hoegen et al, 2002;Li et al, 2015). Recently, Boevink et al (2020) suggested that the sporangiophores of P. infestans commonly emerge through stomata, and this must involve manipulation of stomatal regulation. In this context, our results show that StLTP10 exhibits a cooperative action with PYL4 to regulate stomatal closure during P. infestans infection.…”
Section: F I G U R Ementioning
confidence: 99%
“…5a) and in both avirulent ( Pst ), virulent ( PsthopQ1‐1 ) and Agrobacterium tumefaciens challenges of N. benthamiana , transient expression of effectors or viral proteins such as p50, or following exogeneous application of ROS (Erickson et al ., 2014; Caplan et al ., 2015; Ding et al ., 2019). Pathogen effects on stromule formation and chloroplast–nuclear association is remarkably similar to cROS‐mediated high light responses (Exposito‐Rodriguez et al ., 2017) and oxidative stress imposed by silencing of NTRC (Brunkard et al ., 2015).…”
Section: Cellular Reorganization During Infection Stromules and Perimentioning
confidence: 99%
“…The molecular interaction between phytopathogenic oomycetes and plants is a well-orchestrated and highly dynamic process [287,288,289].…”
Section: Discussionmentioning
confidence: 99%